(untitled) (Ágora de Heterodoxias, 2017)
The present work is based mainly on the harmonic analysis and brief explanation of the play, presented in video, Canto de Ordeño. Tonada by Antonio Estévez, performed by María Irene Escobar Bonaudi and Fausto Castillo Paradas.